Felicjan Sławoj Składkowski i Bogusław Miedziński wobec kwestii żydowskiej w ostatnich latach Drugiej Rzeczypospolitej - Adamczyk, Arkadiusz (Acta Universitatis Lodziensis. Folia Historica, 1999)
A comparison of the attitudes and views of Felicjan Sławoj Składkowski and Bogusław Miedziński – who both were the important persons in the governing camp in Poland before September 1939 – is rare in the Polish literature concerning the modern history. The fact that in the second half of the 1930s, both of them, more or less intentionally, prominently contributed in a creation of the stereotype of Jews in the Polish society is one of the common point of their biographies. This article attempts to show the relations of both those politicians with the Jewish minority by their actions, conducts and official or semi-official statements. The author tries to explain how far the Jewish question was an element of the political tactic of the governing camp in Poland just before the World War II, and to what an extent the addressing of the Jewish problem was the autonomous goal of the real actions. He also explains how far the statements of both of those politicians were representative for their political environment and in what a way they influenced the society. The author considers that the effects of the enunciation of those persons as well as the attitude of the Poles towards the Jews based on it, were exaggerated by far especially by the western historians.